Społeczny wymiar »Energiewende« – rozwój energetyki prosumenckiej w Austrii - Kucharska, Anna (Wydawnictwa AGH, 2018)
Prosumers are the part of new type of society that is being gradually created together with the process of energy transition into environmentally friendly model of energy system based on renewables. Prosumers are active market participants, which benefit from the energy transition. These informed consumers can, through their choices, drive development of green energy and support environment protection. Their active role in energy system entails certain challenges related to the economic and technical issues. Therefore, there is need to implement appropriate legal basis to regulate involvement of consumers on the market as well as to develop new technologies and infrastructure in order to enable them an access to the system. These actions collectively aim to strengthen national economy and ensure security of energy supply.

Prosumenci są nową grupą społeczną, która aktualnie powstaje razem z procesem transformacji energetycznej – przyjaznego środowisku modelu systemu energetycznego, opartego na odnawialnych źródłach energii. Prosumenci są aktywnymi uczestnikami rynku, którzy korzystają z transformacji energetycznej. Jako świadomi konsumenci mogą, poprzez swoje wybory, wpływać na rozwój »zielonej energetyki« oraz wspierać ochronę środowiska. Ich aktywna rola w systemie energetycznym tworzy również określone wyzwania o charakterze ekonomicznym i technicznym. Z tego powodu konieczna jest implementacja odpowiednich podstaw prawnych, regulujących zaangażowanie konsumentów na rynku energii, jak też i rozwój nowych technologii i infrastruktury w celu umożliwienia im dostępu do systemu energetycznego. Te działania łącznie mają na celu wzmocnienie zarówno gospodarki narodowej, jak i bezpieczeństwa dostaw energii.
Social dimensions of »Energiewende« - development of prosumer energy in Austria
Studia Humanistyczne AGH
Keywords: energy transition; prosumer; Austria; renewable resources; energy policy; transformacja energetyczna; prosument; Austria; odnawialne źródła energii; polityka energetyczna